L'inclusione sociale e il dialogo interculturale nei contesti europei - Boffo, Vanna (Proceedings e report, 2008)
The book contains the proceedings of the European conference and review «Products and experiences for intercultural dialogue: Best practices for social inclusion in Italy and Europe" held in Florence on 18 January 2008 in the framework of the project «Social Inclusion: How Leonardo da Vinci Projects Contribueted to Make it Effective». With a social and pedagogic/educational approach, the text is designed to make a specific contribution to the knowledge and evaluation of quality products, carefully selected by European experts, regarding three fundamental aspects of social inclusion and intercultural dialogue: learning on the part of the immigrants of the language and culture of the host country; reception and inclusion in the workplace; the protection of the health and safety of the immigrants.